Water and Wastewater Services in the Danube Region : Austria Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector maturity assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector maturity is included in the annex of the state of the sector regional report from the Danube Water Program. The outcomes of this assessment for the Austrian water sector are presented, which also shows average and best practices in the Danube region. The Austrian sector maturity score is 96, which is significantly higher than the Danube average maturity of 64, and the highest score in the region. The assessment shows that, on average, the country performs very well in terms of access to piped water and flushes toilet, wastewater treatment coverage, customer satisfaction, continuity of service, wastewater compliance, collection ratio, and nonrevenue water.